2010
DOI: 10.1055/s-0030-1255742
|View full text |Cite
|
Sign up to set email alerts
|

Small-bowel capsule endoscopy diagnoses early and advanced neoplasms in asymptomatic patients with Lynch syndrome

Abstract: Curable early or advanced neoplasms in asymptomatic patients with Lynch syndrome using capsule endoscopy can be detected with a better reproducibility than with CT enteroclysis. The clinical usefulness of systematic small-bowel screening in these patients should be confirmed through large prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 11 publications
0
44
1
2
Order By: Relevance
“…CT enteroclysis detected the carcinoma, but missed the two adenomas. Based on these results, the authors concluded that surveillance for small-bowel neoplasia in LS by VCE might be efficient 13. The difference between their and our results may well be due to the much smaller sample size of their study.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…CT enteroclysis detected the carcinoma, but missed the two adenomas. Based on these results, the authors concluded that surveillance for small-bowel neoplasia in LS by VCE might be efficient 13. The difference between their and our results may well be due to the much smaller sample size of their study.…”
Section: Discussioncontrasting
confidence: 66%
“…Saurin et al 13 investigated the prevalence of small-bowel neoplasia in asymptomatic patients with LS by both VCE and CT enteroclysis. In 35 proven gene carriers, histologically confirmed small-bowel neoplasms were detected by VCE in three patients (8.6%): one carcinoma and two adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…Due to ease of the procedure it has become a first line tool to detect small bowel abnormalities in non-obstructed patients for evaluation of small intestinal diseases such as occult GI bleeding, suspected CD, celiac disease, small bowel tumors, and motility disorders [73] . Most VCE studies show the presence of small bowel polyps ranging 50%-87% in patients with FAP [11,12] and there are a few case series suggesting the role of VCE in LS [74,75] . A study comparing VCE to MRI showed the advantage of VCE to detect smaller polyps.…”
Section: Video Capsule Endoscopymentioning
confidence: 99%
“…46 studies of small bowel screening in ls patients are lacking. however, one screening investigation of 35 gene mutation carriers found that 2 had jejunal adenomas and 1 had a jejunal cancer 151 (table 13). six additional patients had capsule endoscopy images of uncertain clinic relevance, prompting additional invasive investigation in 5 patients.…”
Section: Colorectal Cancermentioning
confidence: 99%